Horizontal ridging with mulching as the optimal tillage practice to reduce surface runoff and erosion in a Mollisol hillslope - Yucheng Wang; Dayong Guo; Zheng Li; Wuliang Shi; Bin Li; Liyuan Hou; Yi Zhang; Jinhu Cui; Ning Cao; Yubin Zhang (Agricultural Water Management)
Soil erosion is amplified by the increased precipitation and rainfall erosivity caused by the changing climate, particularly for global mid-high latitude areas. Yet soil erosion processes and proper tillage practices are not well understood at the crop seedling stage, when the annual precipitation is usually concentrated in these regions. Simulated rainfall experiments were conducted at the rainfall intensities of 50- and 100-mm h−1 to investigate the differences in soil erosion of a 5° hillslope during the maize seedling stage between conservation and conventional tillage measures, including cornstalk mulching (Cm), horizontal ridging (Hr), horizontal ridging + mulching (Hr+Cm), vertical ridging + mulching (Vr+Cm), vertical ridging (Vr) and flat-tillage (CK). The results demonstrated that crops, at the seedling stage, can reduce soil erosion by altering the distribution of raindrops and reduce its kinetic energy. Conservation tillage measures significantly reduced total runoff (11.7 %–100 %) and sediment yield (71.1 %–100 %), delayed runoff-yield start time (85 s–26.1 min), decreased runoff velocity (71.5 %–96.7 %), and reduced runoff and soil loss rates, compared to conventional tillage measures. Mulching showed better performance than Hr. It reduced sediment concentration (∼70.6 %–100 %) by reducing runoff velocity and soil particle filtration. The contour ridge ruptured earlier at 100 mm h−1 than at 50 mm h−1 and changed the characteristics of the soil erosion by providing a larger source of sediment for surface runoff. Runoff rate, rather than soil erodibility, was the key factor affecting soil erosion. Decreasing runoff velocity was more important than controlling the amount of runoff. The Hr + Cm treatment exhibited the lowest soil erosion and is recommended for adoption at the maize seedling stage in sloping farmland. Our findings provide an optimized tillage method to mitigate soil erosion in spring in Northeast China.